The Effect Of Exploratory Multimedia Toward Learning Outcomes Of Electrical Power Generation Based On Differences Of Studentsâ Spatial Ability - Sriadhi, Sriadhi (JOURNAL OF EDUCATION SCIENCE, 2015)
Learning multimedia will determine the quality of learning result, and effective multimedia is determined by the arrangement and presentation of materials which use multimedia design principles. Besides, the learning result is also determined by studentsâ spatial ability, particularly in technology learning. This study proves the effect of exploratory multimedia towards the comptence of electrical power generation for memory recall on immediate post-test (M.Rc/I.PT) and memory retention on delayed post-test (M.Rt/D.PT), based on the differences of studentsâ spatial ability.This quasi experiment involves 74 sample of students with Â 32 students are high spatial ability (H.SA) and 42 students are low spatial ability (L.SA). The research result proves that there are significant differences of learning result between group of (H.SA) and group of (L.SA), wheregroup of (H.SA) is higher than group of (L.SA) with differences of mean score 3.50 for Pre Test; 6.50 for (M.Rc/I.PT); and 6.40 for (M.Rt/D.PT). The decrease of learning result on (D.PT) and (I.PT) also have significant difference.